Peran Notaris Dalam Proses Perubahan Anggaran Dasar Perusahaan Guna Mewujudkan Good Corporate Governance - Dewi Ajipawang Setyawati; Budi Santoso (Magister Kenotariatan Universitas Diponegoro, 2023)
Abstract Notaries have the role of a number of matters or conditions related to the company, including as a candidate to propose the legitimacy of a legal element, in order to apply for ratification of changes to the organization's articles of association. A Notary also has a role in amendments to the articles of association and changes in the Notary's organizational information. The research method used is normative juridical and the research specification is descriptive-analytic. The data analysis technique used qualitative analysis. Based on the results of this study, it was found that for every amendment to the Company's Articles of Association, the Notary must make a deed of amendment to the Articles of Association, where this deed is another deed containing changes from the previous Articles of Association. In making the company deed, the substance and statements contained in the organizational contract actually refer to positive law, and still refer to the draft organizational structure, but changes are made in the articles so that they do not conflict with company regulations and principles in order to create a good corporate company. Governance.Keywoards: articles of association; notary; amandmentAbstrak Notaris memiliki peran sejumlah hal atau keadaan yang berhubungan atas perusahaan, termasuk tentang sebagai calon untuk mengajukan legitimasi suatu unsur yang sah, guna permohonan pengesahan perubahan anggaran dasar organisasi. Seorang Notaris juga memiliki peran dalam perubahan anggaran dasar dan perubahan informasi organisasi Notaris. Metode penelitian yang digunakan adalah yuridis normatif dan spesifikasi penelitiannya adalah deskriptifaanalitis. Teknik analisis data menggunakan analisis secara kualitatif. Berdasarkan hasil penelitian ini dihasilkan bahwa untuk setiap perubahan Anggaran Dasar Perseroan, Notaris harus membuat akta perubahan Anggaran Dasar, dimana akta ini merupakan akta lain yang memuat perubahan dari Anggaran Dasar yang lalu. Dalam pembuatan akta perusahaan, substansi dan pernyataan-pernyataan yang terdapat dalam kontrak organisasi sebenarnya mengacu pada hukum positif, dan masih mengacu pada rancangan susunan organisasi, namun dilakukan perubahan dalam pasal-pasalnya sehingga tidak bertentangan dengan peraturan serta prinsip perusahaan agar tercipta perusahaan yang Good Corporate Governance.Kata kunci: anggaran dasar; notaris; perubahan